Use of Pre and post treatment comparison of intra-lesional infiltration of dexamethasone plus hyaluronidase in management of patients with OSMF. - Murmu, Vijaya Bala; Kullu, Ragini (Student's Journal of Health Research Africa, 2024)
Background: Oral Submucous Fibrosis (OSMF) is a chronic, progressive, and potentially malignant disorder characterized by fibrosis of the oral mucosa, leading to trismus and burning sensation. Intralesional injections offer a localized approach to treatment with fewer systemic effects. Aim: To evaluate and compare the pre- and post-treatment outcomes of intralesional dexamethasone and hyaluronidase in the management of OSMF. Materials and Methods: A tertiary care centre conducted one-year prospective interventional research on 50 clinically confirmed OSMF patients. Each patient received biweekly intralesional dexamethasone (4 mg/mL) and hyaluronidase (1500 IU) injections for six weeks. Mucosal flexibility, mouth opening, and VAS were measured before and after therapy. Results: There was a statistically significant increase in mean mouth opening (from 23.4 ± 4.1 mm to 31.2 ± 3.8 mm) and a marked reduction in VAS scores for burning sensation (from 7.3 ± 1.1 to 2.1 ± 0.9). Mucosal flexibility improved in 86% of patients. Conclusion: Intralesional dexamethasone combined with hyaluronidase effectively improves clinical outcomes in OSMF patients, showing significant symptomatic and functional benefits.